2013
DOI: 10.1007/s00384-013-1702-0
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of the LIFT and BIOLIFT procedure: initial experience and short-term outcomes of 33 consecutive patients

Abstract: LIFT and BIOLIFT procedures can be performed safely and effectively in a technically demanding study cohort of predominantly females with complex fistulas. Anterior fistulas have a higher risk of failure but present early and are amendable to repeat procedures. In particular, fistulotomies are useful in downstaged tracts and performing BIOLIFTs is an alternative in the management of LIFT failures and recurrences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…174 The LIFT procedure appears to be a safe and effective sphincter-sparing management option for complex fistulas, with a very acceptable rate of success, even in recurrent disease. Failure is higher in anterior 175 and longer 168 fistulas, but repeat procedures remain feasible. Downstaged tracks may be amenable to fistulotomy.…”
Section: Lift Proceduresmentioning
confidence: 99%
“…174 The LIFT procedure appears to be a safe and effective sphincter-sparing management option for complex fistulas, with a very acceptable rate of success, even in recurrent disease. Failure is higher in anterior 175 and longer 168 fistulas, but repeat procedures remain feasible. Downstaged tracks may be amenable to fistulotomy.…”
Section: Lift Proceduresmentioning
confidence: 99%
“…Only two studies were randomised controlled trials. Likewise, healing rates for the BioLIFT procedure have ranged between 63% and 94% in individual studies, most of which are case series 13 15 16. To our knowledge, this study would be the first systematic review comparing healing rates of BioLIFT versus LIFT.…”
Section: Discussionmentioning
confidence: 99%
“…Anteriorly located fistulae fared significantly worse in their series. 24 The same group from Australia recently published a follow-up study of 13 patients who in total had 16 fistulae. The authors concluded that with the addition of a simple lay-open fistulotomy for subsequent fistulae, the success rate was increased from 68.8% to 81.3%.…”
Section: Complicationsmentioning
confidence: 97%